Spy in the cow shed aids farmers. (Research'eu results magazine)
A growing global appetite for meat has led to farms becoming bigger than ever before. Automatic round-the-clock monitoring of livestock using surveillance technology can help busy farmers better manage their animals, improve the food chain and save money.